Open Regionalism in a World of Continental Trade Blocs - Frankel, Jeffrey (IMF Working Papers; Working Paper, 1998)
Continental trade blocs are emerging in many parts of the world almost in tandem. If trade blocs are required to satisfy the McMillan criterion of not lowering trade volume with outside countries, they have to engage in a dramatic reduction of trade barriers against non-member countries. That may not be politically feasible. On the other hand, in a world of simultaneous continental trade blocs, an open regionalism in which trade blocs undertake relatively modest external liberalization can usually produce Pareto improvement.